Discrepancy between clinical symptoms and electrodiagnostic examination in Guillain Barre syndrome: a case report - Samuel, Ishak; Congdro, Jessica (International Journal of Advances in Medicine, 2025)
Guillain-Barré syndrome (GBS) is an autoimmune disease that targets the peripheral nerves. This case report presents an atypical GBS case with purely motor symptoms but mixed axonal and demyelinating lesions. A 35-year-old man presented with complaints of weakness in four extremities for 2 days before being admitted to the hospital. Four days prior, patient vomited. Motor strength in upper and lower extremities was 3334/4333 and 2334/4332, respectively. Physiological and pathological reflexes were absent in all four extremities. Sensibility was within normal limits. Cerebrospinal fluid (CSF) analysis revealed albumin-cytologic dissociation. Nerve conduction velocity (NCV) examination indicated motor polyneuropathy in 3 extremities, with axonal and demyelinating lesions. Patient was diagnosed with GBS, acute inflammatory demyelinating polyneuropathy (AIDP) subtype. AIDP is the most common subtype of GBS. The patient in this case only had motor symptoms which could occasionally happen in AIDP. However, NCV studies revealed axonal and demyelinating lesions. This discrepancy could be due to secondary axonal degeneration that had been reported in demyelinating neuropathies. Initial mixed pattern had also been reported to evolve into other subtypes during serial electrodiagnostic evaluations. The discrepancy can complicate the diagnosis and further observation may be needed. Patient in this case report improved spontaneously with supportive treatment. GBS is a complex disease to diagnose and manage due to its heterogeneous clinical presentation and variable prognosis. This case report presents an AIDP-subtype GBS patient with purely motor symptoms but mixed demyelinating and axonal lesions. Further electrodiagnostic examination might be needed to establish a diagnosis.